(Not Your) Grandpa's Church Service: Pyrotheology's Familial Resemblance to Liberal Theology and the Possibilities for Political Liturgy. Issue 4 (October 2016) - Osinski, Keegan
Abstract : This article explores the relationship between the liberal theology of the late nineteenth and early twentieth centuries and Peter Rollins's Pyrotheology, which I present here as a theological methodology that encourages the questioning of beliefs and the embracing of doubt. I highlight the family resemblances between these two theologies, focusing on their emphasis on individual experience and their engagement with society and culture. I explore how liberal theology might be emboldened by the deconstructive spark of Pyrotheology, and how Pyrotheology might be enriched by the social justice torch of liberal theology. I argue that the pyrotheological liturgical practice of Transformance Art could be the site of a more constructive engagement between Pyrotheology and liberal theology, serving to move the former's often inward focus toward more outward work for justice in the world.